The impact of sports activities on narrative psychology from the perspective of Caring ethics - Yile Wang; Junmiao Deng, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study uses narrative and positive psychology as its theoretical foundations to investigate the impact of sports activities on young people's mental health. Class 1 and Class 2 students of the Department of Economics and Management in the Modern College of Arts and Sciences of a normal university, as well as some front-line Physical Education (PE) instructors and ideological and political teachers of a normal university, were surveyed. This study utilized a questionnaire to collect information from respondents. Smart PLS 4.0 is used to analyze the data for this study. This study found that, from the perspective of compassionate ethics and in the context of the COVID-19 pandemic, physical activity can promote the mental health of adolescents, most notably by reducing anxiety, stress, depression, and feelings of isolation. This study determined that physical activity promotes the healthy growth of adolescent narrative psychology. Furthermore, physical activity significantly impacts adolescents' mental health, which can reduce adolescent ennui, boredom, and the risk of depression. Moreover, it can reduce stress, alleviate anxiety, and enhance adolescents' sleep quality. In addition, it can improve adolescents' mental health, cognitive health, thinking, learning, and general well-being.